Models Of Improving The Quality Of Education In World Experience - Muxammadjonov, Muslimbek (International Conference on Global Trends and Innovations in Multidisciplinary Research, 2025)
This research explores global models aimed at improving the quality of education, focusing on best practices implemented in developed countries such as the United States, Finland, South Korea, and Singapore. The study analyzes key aspects of these models, including effectiveness, innovative approaches, increasing the efficiency of the learning process, professional development of teachers, and improvement of assessment systems. It also examines the recommendations of international organizations such as UNESCO and OECD (particularly PISA assessments) in enhancing education quality. The paper concludes with proposals for adapting the most suitable international models to the context of the Uzbek education system.